MENINGKATKAN MINAT BACA PESERTA DIDIK MELALUI METODE QUANTUM READING DALAM MATA PELAJARAN BAHASA INDONESIA - Imas Nenden Kuraesin; Nana Suryana; Nita Anjung Munggaran (Latifah Pres, 2019)
This research is based on findings in the field, namely students' low interest in reading, no initiative to read books, less reading activities, and less supportive library facilities. The formulation of the problem in this study is how to increase the reading interest of students who use quantum reading methods and conventional methods in Indonesian language subjects at Pakemitan 2 Public Elementary School. This study aims to determine the increase in reading interest of students who use quantum reading methods and conventional methods in Indonesian language subjects at Pakemitan 2 Public Elementary School. The research method used is the experimental method with the Nonequivalent Control Group Design form. The population used was 165 students, and two sample classes were class IV as a control class totaling 28 students and class V as an experimental class totaling 35 students. Research data was collected through questionnaires with statistical analysis. Analysis of the data used is normality test, homogeneity test, and hypothesis testing using SPSS version 24.0 for windows. The results of the analysis of variable X, it is known that the control class pre-test value obtained an average value of 53.92 is in the low classification, and the experimental class pre-test value obtained an average value of 55.94 is in the low classification. As for the value of the post-test control class obtained an average value of 58.46 in the low category, this shows the implementation of the conventional method has not been successful, and the post-test value of the experimental class obtained an average value of 67.34 in the category quite effective, this shows the implementation of the quantum reading method is quite successful. The results of the variable analysis Y, it is known that the control class pre-test value obtained an average value of 55.07 is in the low classification, and the experimental class pre-test value obtained an average value of 55.57 is in the low classification. As for the value of the post-test control class obtained an average value of 60.03 in the low category, this shows the implementation of the conventional method has not been successful, and the post-test value of the experimental class obtained an average value of 68 in the category quite effective, this shows the implementation of the quantum reading method is quite successful, then Hₒ is rejected or Hₐ is accepted. That is, the use of the quantum reading method can increase the reading interest of elementary school students in Indonesian subjects.